Improving reliability in NoCs by reconstructing location distribution of management cores. (August 2019) - Fu, Fangfa; Lou, Binglei; Chen, Yukun; Wang, Jinxiang
Abstract: Currently, most of fault-tolerance mechanism of NoC systems with hierarchical management structure has not discussed the influence of the location distribution of management cores on the reliability of NoCs. In this paper, based on the role-changeable fault-tolerant management (RCFTM) platform that is a kind of hierarchical management structure, the influence of the location distribution of management cores on the reliability of NoC system is further studied. At the same time, an improved ant colony optimization for fault tolerance algorithm named ACOFT is proposed to make the NoC system automatically generate a better location distribution scheme and finish the fault-tolerance process. It has been verified that the location distribution scheme of management cores generated by ACOFT can help the system achieving lower energy consumption than RCFTM method based on different system scales between 4 × 5 to 9 × 10 2D-mesh structure, and the reduction of energy consumption is ranging from 20% to 42%.